Dampak Pekerja Migran Ilegal Terhadap Meningkatnya Kasus Human Trafficking Di Pulau Lombok - Lalu Maulana Ukhrowi; Lalu Puttrawandi Karjaya; Muhammad Sood (The Department of International Relations Universitas Mataram, 2020)
This thesis aims to analyze the increasing cases of human trafficking on the island of Lombok as a result of the large number of people in Lombok becoming illegal migrant workers. The case of human trafficking on the island of Lombok is one of the studies of national security issues since the beginning of the 20th century. The core of this problem is the occurrence of cases of human trafficking which still increase until the end of 2019 as a result of many people of Lombok choosing to become illegal migrant workers. The spotlight issue in this paper is the reason why the Lombok people chose to become illegal migrant workers and the impact of the large number of illegal migrant workers on the increasing cases of human trafficking in Lombok. The important role of the Government of Indonesia and the Regional Government in facing and responding to this case is seen from the perspective of Non-Traditional Security.